IPv6 Essentials - Hagen, Silvia, 1965- (Sebastopol, California : O'Reilly Media, Inc., 2016)
With the continuing eruption of Internet-enabled devices - smartphones, tablets, PCs, cars, infusion pumps, refrigerators, earthquake detectors, and thousands of other gadgets - the 30 year-old IPv4 communications protocol is straining under the weight. This book gets you up to speed on IPv6, the long-awaited revision that offers 128-bit addresses to replace IPv4's outdated 32-bit system. For nearly a decade, IPv6 has been just two years away . Finally, the future has arrived. The new version is ready, it works, and momentum is starting to build. This thoroughly revised third edition of IPv6 Essentials provides a succinct, in-depth update of the latest features and functions in IPv6, guiding you through everything you need to know to get started. Ideal for system and network administrators, engineers, network designers, and IT managers, this book will help you plan for, design, and integrate IPv6 into your current IPv4 infrastructure.
Includes index.
foreword by Vint Cerf.
Keywords: TCP/IP (Computer network protocol).; Computer network protocols; Multicasting (Computer networks).